International surrogacy as disruptive industry in Southeast Asia - Whittaker, Andrea (Andrea M.), 1967- (Medical anthropology (New Brunswick, N.J.), 2019)
"Over the last 15 years or so, a new trade in assisted reproduction has grown across the world, offering people the opportunity to form families through cross-border exchanges of gametes, embryos, and gestational surrogates. This trade has been aided by the advent of affordable transport, information technologies, and the movement of assisted reproductive expertise around the world, combined with regulatory differences between different jurisdictions that make it possible for people to circumvent restrictions in their home countries to pursue their imagined families elsewhere. However, the growth of this industry has thrown into relief older forms of inequality by class, race, or economic status, and poses new questions about the social impact of these technologies and the new opportunities and threats they pose to women, particularly poorer women from developing countries, whose bodies are the sources of these products. International Surrogacy as Disruptive Industry in Southeast Asia traces the rise and fall of surrogacy as a commercial service in Thailand. Thailand had been a popular destination for commercial surrogacy from 2011 until the 'Baby Gammy' case in 2014, which caused the military government of Thailand to ban the practice in 2015. Since its closure in Thailand, the industry has moved to other countries in the region, such as Cambodia, which lack any current regulations or legislation. This fascinating ethnography brings to light the lives of the intended parents, the doctors, brokers, and regulators in Thailand, to show how this amazing opportunity for some also offers the potential for exploitation of vulnerable groups of people in the absence of adequate protections"--